Pengembangan Sistem Pemantauan Distribusi Laporan Berbasis Web - Kurniadi, Andry; Yasin, Verdi; Sianipar, Anton Zulkarnain (STMIK Banjarbaru, 2026)
The Judicial Commission of the Republic of Indonesia faces challenges in monitoring and distributing public reports, which are still conducted manually and therefore lack effectiveness and integration. This study aims to develop a web-based Report Distribution Monitoring System Module to improve the effectiveness, efficiency, and transparency of report management within the Supervision Service Unit. The system was developed using the Rapid Application Development (RAD) method, which includes the stages of requirements planning, user design, construction, and cutover. The system was implemented as a web-based application using PHP as the programming language and MySQL as the database. System testing was carried out using black box testing involving Super Admin, Admin, and User roles to evaluate functional suitability. The test results indicate that all main system features operate in accordance with user requirements. Therefore, the developed system is considered feasible to support structured and integrated monitoring and distribution of public reports.Keywords: Judicial Commission; Bureaucratic Reform; Report Distribution Monitoring System Module; PHP; MySQLAbstrakKomisi Yudisial Republik Indonesia menghadapi tantangan dalam pemantauan dan pendistribusian laporan masyarakat yang masih dilakukan secara manual sehingga kurang efektif dan terintegrasi. Penelitian ini bertujuan mengembangkan Modul Sistem Pemantauan Distribusi Laporan Berbasis Web guna meningkatkan efektivitas, efisiensi, dan transparansi pengelolaan laporan pada Unit Layanan Pengawasan. Pengembangan sistem dilakukan menggunakan metode Rapid Application Development (RAD) yang meliputi tahap requirements planning, user design, construction, dan cutover. Sistem dikembangkan berbasis web menggunakan bahasa pemrograman PHP dan basis data MySQL. Pengujian sistem dilakukan melalui metode black box testing dengan melibatkan pengguna Super Admin, Admin, dan User untuk menguji kesesuaian fungsi sistem. Hasil pengujian menunjukkan seluruh fitur utama berjalan sesuai kebutuhan pengguna. Dengan demikian, sistem yang dikembangkan dinyatakan layak digunakan sebagai sarana pendukung pemantauan dan distribusi laporan masyarakat secara terstruktur dan terintegrasi.